Малокутове розсіяння нейтронів в дослідженні біцел та протеобіцел з інкорпорованою мітохондреальною цитохромоксидазою - Siposova, K.; Petrenko, V. I.; Ivankov, O. I.; Bulavin, L. A.; Musatov, A. (Publishing house "Academperiodika", 2020)
The structural investigations of a model membrane system, bicelles, and the aggregation state of isolated and purified bovine heart cytochrome c oxidase (CcO) in bicelles have been performed using small-angle neutron scattering (SANS), SANS contrast variation, and complemented by various biophysical and biochemical techniques. The average size of bicelles prepared from long-chain 1,2-dimyristoyl-sn-glycero-3-phosphocholine and short-chain 1,2-dihexanoyl-sn-glycero-3-phosphocholine was found to be about 22 nm with a thickness of about 4 nm. Enzyme in bicelles was remained active and structurally unaltered. The estimated volume of protein in bicelles of 240 nm3 corresponded well to the monomeric form of CcO. The ab initio modeling supports the experimental data and suggests that CcO in bicelles is a homogeneous monomeric complex incorporated into bicelles.